2015
DOI: 10.1016/j.steroids.2015.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol metabolites exported from human brain

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 28 publications
0
60
0
3
Order By: Relevance
“…Heverin et al (42) have shown that 26-HC is imported to the brain, whereas Meaney et al (43) have shown that its acidic metabolite 7αH,3O-CA is exported from the brain to circulation. Further studies by Iuliano et al (44) have shown that a precursor of this acid, 7α,26-dihydroxycholest-4-en-3-one (7α,26-diHCO), is also exported from the brain to circulation, as is its isomer 7α,25-diHCO. In another study, Ogundare et al (45) have shown that multiple parts of the acidic pathway of bile acid biosynthesis are active in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Heverin et al (42) have shown that 26-HC is imported to the brain, whereas Meaney et al (43) have shown that its acidic metabolite 7αH,3O-CA is exported from the brain to circulation. Further studies by Iuliano et al (44) have shown that a precursor of this acid, 7α,26-dihydroxycholest-4-en-3-one (7α,26-diHCO), is also exported from the brain to circulation, as is its isomer 7α,25-diHCO. In another study, Ogundare et al (45) have shown that multiple parts of the acidic pathway of bile acid biosynthesis are active in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…OS were determined by high performance gas chromatography coupled to mass spectometry (GC-MS) detection using deuterium-labelled internal standards, as described previously Iuliano et al [25]. Briefly, 10 µl butylated hydroxytoluene (BHT) in ethanol (5 mg/ml) and 50 µl EDTA (10 mg/ml) were added to a solution of 1 ml plasma and [26]. A list of the OS measured is provided in…”
Section: 3measure Of Os Concentrationsmentioning
confidence: 99%
“…respectively, at position C-24 [1,2]. Supplementation of foods with 60 plant sterols and daily intake of 2 g plant sterol esters leads to a 61 nearly 10% lowering of cholesterol in the blood and a slight 62 increase of the serum levels of these plant sterols [1,3] [10]. The same group recently reported on flux of unesteri-83 fied 7a-25-and 7a-(25R)26-dihydroxycholesterol from the brain 84 into the periphery [11] from the same material.…”
mentioning
confidence: 99%